Workplace ostracism and helping behavior: a cross-level investigation - Huang, Wenyuan (Journal of business ethics, 2024)
Prior research on workplace ostracism and helping behavior has yielded mixed results. This study integrates social learning theory and social role theory by constructing a multilevel model to examine the relationship between supervisor ostracism and helping behavior that focuses on the mediating role of coworker ostracism and the moderating role of subordinate gender. Using a two-wave, multisource approach, data were collected from 382 employees and 43 immediate team leaders in four business corporations in Guangxi Province, China. The results of path analysis reveal that supervisor ostracism has a cross-level effect on helping behavior through the mediating role of coworker ostracism. Furthermore, the positive direct effect of supervisor ostracism on coworker ostracism and the negative cross-level indirect effect of supervisor ostracism on helping behavior via coworker ostracism was stronger for men than women. These findings expand and deepen our understanding of the ostracism field.